Description of the Implementation of Care Continuum Treatment for Relapse in Cancer Survivors: Gambaran Implementasi Care Continuum Treatment Untuk Relaps Pada Penderita Kanker - Aminah, Ai; Afiyanti, Yati; Santosa, Puji Raharja (Alauddin Scientific Journal of Nursing, 2023)
Background: Cancer is a disease that can affect almost any organs or tissues of the body characterized by abnormal cells growing uncontrollably. Cancer sufferers undergo a series of treatments, either surgery, chemotherapy, radiation or a combination of the two, adjusted to the patient’s own clinical condition. , type of cancer, stage of cancer . Cancers that have completed a series of treatments and nursing will then be declared in stable condition and evaluated based on the guidelines of each science. Recurrence or relapse cancer is cancer that is found after treatment is complete and monitored for a different period of time in each cancer survivors and the type of relapses can occur in the original place or can arise in distant places. In carrying out care continuum care for cancer survivors it is not only physical problems but care continuum care which also includes psychological, social and spiritual care from assessment to evaluation involving the family. Purpose: The researcher conducted a literature review which aims to find out an overview of the implementation of treatment care continuum on the incidence of relapse in cancer survivors.The method used in this writing is Literature Review with IMRAD ( Introduction,Method,Result, and Discussion ) and then we analysis using the PRISMA (Preferred Reporting Items For Systematic Reviews and Meta Analyzes) method with a total of 9 article sources. Results: Based on studies that have been reviewed, it was found that the application of care continuum care for survivors cancer has an important role in minimizing the incidence of cancer relapse and can improve the health of cancer survivors. Conclusion: The implications of applying care continuum are expected to be applied on an ongoing basis to cancer survivors, in an effort to monitor and reduce the incidence of relapse in cancer survivors.